SARANA PENDIDIKAN MENURUT AL-QURAN - Darliana Sormin; Adek Kholijah Siregar (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Educational facilities are a component of education, this is an important component in realizing success in the learning process. Learning media or learning tools are educational tools. Educational facilities according to education experts are very diverse, but in this article the author only discusses educational facilities that are directly involved in the learning process and do not include infrastructure such as classrooms, in this article the author takes existing educational facilities described or strengthened by the verses of the Koran and explained its function by the interpreters. So that this facility becomes feasible to be a component of education, especially in Islamic education. Keywords: facilities, education, the Koran